Development of multi-cylinder linear machine powertrain system for electric vehicle - Mohamed Noor, Norramlee (2021)
Electric vehicles (EVs) have been recognized as a crucial pillar of a solution to significantly mitigate the detrimental impacts of transportation while improving energy consumption efficiency. Electric machines are classified into two types: rotational machines and linear machines. These EVs utilize rotating electric machines to transmit power from the motor shaft to the transmission and, subsequently, to the wheels through differential gears. However, the electric rotating machines of EV are expensive, have a complicated control system, heavy weight and must be larger in size to run the vehicle. Furthermore, the rotating electric motor of EVs suffers from excessive exposure temperature due to lengthy operation, which may cause the motor to fail, while the magnet is expensive. They also necessitate a specialised power transmission system in order to run the vehicle. This will increase the cost of the cars. On the other hand, the disadvantage of an internal combustion engine (ICE) is the friction between the piston rings, piston skirt, and cylinder linear that needs much effort to overcome friction, to outperform fuel efficiency. Therefore, a new proposed linear machine, known as the multi-cylinder linear motor powertrain system (McLMPS), has been conceived and developed to minimize the weight, size, and fuel consumption of the ICE. The McLMPS does not require the use of a specific power transmission system to verify its performance in the EV. The McLMPS prototype comprises various parts, namely a multi-cylinder linear machine (McLM), a multi-plate crankshaft position sensor (MpCPS) system, other mechanical components, and the drive system, which includes a control unit and a machine operating algorithm. The proposed McLM structure was selected due to its simple structure, high thrust, lack of a magnet, and minimal cogging force issue. The proposed McLMPS was simulated using MATLAB/Simulink. The high level class was simulated used current about 250A at 300V battery supply, the plunger output force was 55.1kN with a torque of about 97.5Nm and motor power was about 67.5kW. From the simulation results, the efficiency of the proposed McLMPS was about 90%, whereas the experimental results has an efficiency of around 75%. The experimental results show lower efficiency compared to simulation results because the first prototype of McLMPS was built based on quarter scale. On the other hand, the experimental results of the McLMPS is more efficient than the Perodua Kancil ICE, but less efficient than the Renault Zoe EV.